The playmaker's advantage how to raise your mental game to the next level - Zaichkowsky, Leonard D. 1944-; Peterson, Daniel (Author/consultant in athlete development) (Gallery Books/Jeter Publishing, 2018)
Discover how to improve your mental game--the next frontier in sports training--to become the Playmaker on the court, rink or field. Coaches search for it. Parents dream of it. Fans love it. Athletes want it. The Playmaker on any sports team possesses it: an elusive, intangible quality combining anticipation, perception, and decision-making skills. This quality raises their game above the competition and allows them to pass when no one else can, anticipate the movement of opponents, and avoid costly mental mistakes, thus holding the team together. Using today's technology and tools, it is now possible to understand, assess, and train this sixth sense rather than just hope it magically appears. Now, for the first time, cognitive science research is revealing the secrets of the Playmaker's keen sense of awareness. Just as tests of speed, strength, and agility have provided a baseline of physiological biomarkers, youth sports coaches can now capture cognitive metrics including attention, pattern recognition, anticipation, and the ability to take quick, decisive action during the chaos of competition. The Playmaker's Advantage is a groundbreaking book that will educate developing athletes, along with their parents and coaches, about this essential creative capability in an accessible, easy to understand method.